Makna Kesetaraan Gender dagi Followers Instagram @wmnlyfe - Karnanto, Natasya Yolanda Poetri; Utamidewi, Wahyu; Nurkinan, Nurkinan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The issue of gender equality is one of the issues that still often occurs, especially in Indonesia. One of the things that underlies this gender inequality occurs because of the inherent patriarchal culture which shows that men tend to hold greater power roles so that it indirectly degrades the existence of women. In order to be free from the oppressive patriarchal culture, men's participation is also considered necessary in an effort to increase public awareness about gender equality. The involvement of mass media, namely Instagram, is also able to play a considerable role in efforts to voice issues regarding gender equality. The research method used is a descriptive qualitative method with in-depth interviews with informants who are followers of @wmnlyfe. The results of this study will explain how individuals interpret gender equality contained in the campaign video